Logarithmically Improved Regularity Criteria for a Fluid System with the Linear Soret Effect - Minglei Zang; Xiaoyan Guan (Abstract and Applied Analysis)
We consider the 3D fluid system with the linear Soret effect. We obtain a logarithmically improved regularity criterion in the BMO space.